2023
DOI: 10.1590/acb384623
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin promotes hypertrophic scar repair by autophagy of hypertrophic scar-derived fibroblasts

Qing Zhang,
Maomao Wang,
Xingwang Deng
et al.

Abstract: To investigate the Shikonin (SHI) induce autophagy of hypertrophic scar-derived fibroblasts (HSFs) and the mechanism of which in repairing hypertrophic scar. Methods: This study showed that SHI induced autophagy from HSFs and repaired skin scars through the AMPK/mTOR pathway. Alamar Blue and Sirius red were used to identify cell activity and collagen.Electron microscopy, label-free quantitative proteomic analysis, fluorescence and other methods were used to identify autophagy. The differences in the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…58 The promotion of autophagy in HSF cells by shikonin may be attributed to the AMPK/mTOR signal pathway, offering novel insights into hypertrophic scar treatment. 59 In this study, the integrative analysis of the lactylome and proteome revealed that hypertrophic scar tissues exhibited a significant upregulation of 14 lactylation sites. Our particular focus was on the lactylated GATM at K102.…”
Section: ■ Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…58 The promotion of autophagy in HSF cells by shikonin may be attributed to the AMPK/mTOR signal pathway, offering novel insights into hypertrophic scar treatment. 59 In this study, the integrative analysis of the lactylome and proteome revealed that hypertrophic scar tissues exhibited a significant upregulation of 14 lactylation sites. Our particular focus was on the lactylated GATM at K102.…”
Section: ■ Discussionmentioning
confidence: 77%
“…It is well-established that hypoxia, leading to the induction of hypoxia-inducible factor-1 alpha (HIF-1alpha), contributes to scar formation during the healing of cutaneous wounds . The promotion of autophagy in HSF cells by shikonin may be attributed to the AMPK/mTOR signal pathway, offering novel insights into hypertrophic scar treatment …”
Section: Discussionmentioning
confidence: 99%
“…Shikonin has a role in inducing ROS, suppressing the release of exosomes, and inducing apoptosis [309]. Shikonin inhibits the expression of p63 (a type II integral membrane protein), cytokeratin 10, α-SMA, TGF-β1, and collagen I, which play important roles in HTS formation, suggesting that shikonin has potential utility as a novel scar therapy [310]. Also, shikonin promotes HTS repair via the autophagy of HTS-derived fibroblasts, where the potential mechanism may be related to the AMP-activated protein kinase/mammalian target of rapamycin (mTOR) signal pathway [311].…”
Section: Shikoninmentioning
confidence: 99%
“…Orally administered saireito can reduce postoperative edema after blepharoptosis surgery by suppressing TGF-β1-induced Smad 2/3 phosphorylation [254,314]. Shikonin inhibits the expression of p63, cytokeratin 10, α-SMA, TGF-β1, and collagen I [310].…”
Section: Peripheral Vasodilator Pentoxifyllinementioning
confidence: 99%